Takayasu's arteritis and secondary membranous nephropathy: an exceptional association. Issue 3 (1st March 2021) - Enos, Daniel; Labarca, Gonzalo; Hernandez, Mariel; Mendez, Gonzalo P
Abstract : The association between Takayasu's arteritis and membranous nephropathy is uncommon. We present the case of a 46-year-old man with Takayasu's arteritis treated over 10 years by a multidisciplinary medical team. He had an atrophic left kidney due to arterial stenosis, with a basal creatinine of 1.59 mg/dL (140.55 µmol/l). Three years ago, he presented with full nephrotic syndrome, uncontrolled blood pressure, creatinine increases to 4.5 mg/dL (basal: 1.59 mg/dL), severe hypoalbuminaemia (1.4 g/dL) and albuminuria of 24.6 g per day. He underwent percutaneous biopsy of the right kidney that showed membranous nephropathy with negative PLA2R1 and positive IgG 1, 3 and 4 subclasses. After therapy with oral prednisone and cyclophosphamide, the patient's kidney function improved, without recurrence of disease after 3 years of follow-up. Here, we present this extremely uncommon association of Takayasu's arteritis and membranous nephropathy.